2003
DOI: 10.2307/20062822
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Update: Spanish on the South Texas Border

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Association of Teachers of Spanish and Portuguese is collaborating with JSTOR to digitize, preserve and extend access to Hispania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Mejías and Anderson (1988) and Mejías et al (2003) surveyed the attitudes of heritage Spanish speakers in the Lower Rio Grande Valley of Texas toward the study and maintenance of Spanish. Mejías and Anderson (1988) and Mejías et al (2003) surveyed the attitudes of heritage Spanish speakers in the Lower Rio Grande Valley of Texas toward the study and maintenance of Spanish.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Mejías and Anderson (1988) and Mejías et al (2003) surveyed the attitudes of heritage Spanish speakers in the Lower Rio Grande Valley of Texas toward the study and maintenance of Spanish. Mejías and Anderson (1988) and Mejías et al (2003) surveyed the attitudes of heritage Spanish speakers in the Lower Rio Grande Valley of Texas toward the study and maintenance of Spanish.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Because Spanish in the United States is of special interest in the present study, a summary of some of the previous literature regarding attitudes toward the study of Spanish is warranted. Mejías and Anderson (1988) and Mejías et al (2003) surveyed the attitudes of heritage Spanish speakers in the Lower Rio Grande Valley of Texas toward the study and maintenance of Spanish. Administering the survey in two different years, the investigators found consistent positive attitudes toward Spanish for communication reasons.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…En cambio, el español "para tener más amigos hispanos" es más importante en Los Ángeles que en Miami o San Antonio (Ramírez, 2000). Las actitudes sobre el español en el sur de Texas, por ejemplo, se han mantenido constantes a través de las últimas dos décadas, desde 1982 hasta 2000 (Mejías, Anderson-Mejías y Carlson, 2003) Existen trabajos (Torres, 1997) que han demostrado que es en la propia condición bilingüe donde se ven los principales signos de identidad etnolingüística y no en la lealtad o preferencia hacia una de las dos lenguas. Es por eso, por lo que fenómenos del discurso bilingüe, como la conmutación de códigos, desempeñen un papel decisivo (Blas-Arroyo, 2005, p. 360).…”
Section: Pone De Relieveunclassified